Pengaruh Perilaku Phubbing Terhadap Intensitas Komunikasi Pada Pengunjung di Area Publik M Bloc Space - Fatimah Salsabilla; Budiaman Budiaman; Achmad Nur Hidayaht (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
The study aims to find out the influence of phubbing behavior with communication intensity on visitors in the public area of M Bloc Space. The design of the study uses quantitative research with sampling techniques used with accidental samplings. The sample in this study is a visitor to the public area of M Bloc Space as an active smartphone user with a total of 70 respondents. The data collection method used is a scale of phubbing behavior and communication intensity. The results of this study show that Phubbing behavior has a positive and significant influence on Communication Intensity because the t count value is greater than the t table and the significant value is less than 0.05 so the Ha hypothesis is accepted.